Réponses

2014-10-07T17:30:42+02:00
A= (4x =4)a la puissance 2 - (-x-3)(4x-4)
  =(4x-4)a la puissance 2 -(-x -3)(4x-4)
  =(4x-4)(4x-4-(-x-3)
  =(4x-4)(4x-4+x+3)
  =(4x-4)(5x-1)
B=(3x+4)(4x+10)+(2x+5)a la puissance 2
  =(3x+4)2(2x+5)+(2x+5)a la puissance 2
  =(2x+5)(2(3x+4)+((2x+5))
  =(2x+5)(6x+8+2x+5)
  =(2x+5)(8x+13)
C=(5x-4)a la puissance 2 - (6x-3)a la puissance 2
  =((5x-4)-(6x-3))((5x-4)+(6x-3))
  =(5x-4-6x+3)(5x-4+6x-3)
  =(-x-1)(11x-7)
D=9-(10x-8)a la puissance 2
  =(3-(10x-8))(3+(10x-8))
  =(3-10x+8)(3+10x-8)
  =(-10x+11)(10x+5)
E=4(3x-6)(5x+1)-2(3x-6)a la puissance 2
  =(3x-6)(4(5x+1)-2(3x-6))
  =(3x-6)(20x+4-6x+12)
  =(3x-6)(14x+16)